2023
DOI: 10.1021/acs.nanolett.3c02380
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Thermal Shock Synthesis and Porosity Engineering of 3D Hierarchical Cu–Bi Nanofoam Electrodes for Highly Selective Electrochemical CO2 Reduction

Songyuan Yang,
Huaizhu Wang,
Yan Xiong
et al.

Abstract: Massive production of practical metal or alloy based electrocatalysts for electrocatalytic CO2 reduction reaction is usually limited by energy-extensive consumption, poor reproducibility, and weak adhesion on electrode substrates. Herein, we report the ultrafast thermal shock synthesis and porosity engineering of free-standing Cu–Bi bimetallic nanofoam electrocatalysts with 3D hierarchical porous structure and easily adjustable compositions. During the thermal shock process, the rapid heating and cooling steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Attributed to the highly porous and proper proportion, the Cu 4 Bi nanofoam exhibited a high formate selectivity of 92.4 % at À 0.9 V(vs RHE). [40] As previously reported, the Bi-based catalyst can provide a high FE of formate/formic acid (> 90 %). However, the properties of the active site for Bi-based materials during CO 2 !formic reaction is still controversial.…”
Section: Bi-based Electrocatalystsmentioning
confidence: 53%
“…Attributed to the highly porous and proper proportion, the Cu 4 Bi nanofoam exhibited a high formate selectivity of 92.4 % at À 0.9 V(vs RHE). [40] As previously reported, the Bi-based catalyst can provide a high FE of formate/formic acid (> 90 %). However, the properties of the active site for Bi-based materials during CO 2 !formic reaction is still controversial.…”
Section: Bi-based Electrocatalystsmentioning
confidence: 53%
“…More specifically, bimetallic Zn–In and Zn–Sn catalysts have been extensively studied for the formate production . Bismuth (Bi) has also gained attention due to its higher stability, low toxicity, and cost effectiveness. Bi-based catalysts that have been previously reported were mainly bimetallic CuBi catalysts , or Bi nanoparticles deposited on different carbon supports. , Yang et al synthesized Cu–Bi nanofoam catalysts with a three-dimensional porous structure by the thermal shock method and porosity engineering, showing that the mass transfer kinetics was enhanced and the overpotential for CO 2 RR to formate was decreased . Zhang et al showed that mass transport could also be facilitated by the nanoconfinement effect using bismuth nanorods filled in nitrogen-doped carbon nanotubes .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, the limited mass transfer of CO 2 in aqueous electrolytes due to its low solubility (∼34 mM) and diffusion coefficient (∼1 × 10 −5 cm 2 s −1 ) significantly suppresses the activity of the aqueous-phase CO 2 RR with the current density being restricted in the range of tens of mA cm −2 . 17–19 Moreover, the competitive hydrogen evolution reaction (HER) in aqueous solutions further decreases the selectivity of the CO 2 RR. 20–22…”
mentioning
confidence: 99%